2013
DOI: 10.1007/s12010-013-0324-x
|View full text |Cite|
|
Sign up to set email alerts
|

Enantioconvergent Biohydrolysis of Racemic Styrene Oxide to R-phenyl-1, 2-ethanediol by a Newly Isolated Filamentous Fungus Aspergillus tubingensis TF1

Abstract: An effort was made to isolate biocatalysts hydrolyzing epoxides from various ecological niches of northeast India, a biodiversity hot spot zone of the world and screened for epoxide hydrolase activity to convert different racemic epoxides to the corresponding 1, 2-vicinal diols. Screening of a total of 450 microorganisms isolated was carried out using NBP colorimetric assay. One of the strains TF1, after internal transcribed spacer sequence analysis, identified as Aspergillus tubingensis, showed promising enan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These findings demonstrated that the MIP@g-C 3 N 4 nanocomposites were capable of catalytically activating the H 2 O 2 to form ˙OH radicals in a peroxidase-like catalytic reaction, which subsequently play critical roles in oxidizing TMB to produce a TMB oxide with a blue color. 57 The peroxidase-like catalytic mechanism of MIP@g-C 3 N 4 nanocomposites was proposed and is illustrated in Scheme 2. During the catalytic oxidation reaction, the MIP@g-C 3 N 4 nanocomposites have the potential to operate as peroxidase mimics, which will help facilitate the transfer of electrons between TMB and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These findings demonstrated that the MIP@g-C 3 N 4 nanocomposites were capable of catalytically activating the H 2 O 2 to form ˙OH radicals in a peroxidase-like catalytic reaction, which subsequently play critical roles in oxidizing TMB to produce a TMB oxide with a blue color. 57 The peroxidase-like catalytic mechanism of MIP@g-C 3 N 4 nanocomposites was proposed and is illustrated in Scheme 2. During the catalytic oxidation reaction, the MIP@g-C 3 N 4 nanocomposites have the potential to operate as peroxidase mimics, which will help facilitate the transfer of electrons between TMB and H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…An interesting enantioconvergent process with whole cells of Aspergillus tubingensis TF1 was recently described by Duarah et al [87]. (R)-Phenyl-1,2-ethanediol was isolated from the reaction mixture in 97% ee after 45 min, reaching >99% conversion of racemic SO (8.75 mM).…”
Section: Styrene Oxidementioning
confidence: 99%
“…Using SO as a substrate mimic, SgcF and NcsF2 were shown to be enantiocomplementary, leading to the formation of (R)phenyl-1,2-ethanediol in 99% ee and 87% yield from racemic SO (14 mM) when used together in the reaction mixture (Lin et al, 2010). An interesting enantioconvergent process with whole cells of Aspergillus tubingensis TF1 was very recently described by Duarah et al (Duarah et al, 2013). (R)-phenyl-1,2-ethanediol was isolated from the reaction mixture in 97% ee after 45 min, reaching >99% conversion of racemic SO (8.75 mM).…”
Section: Styrene Oxidementioning
confidence: 99%
“…The kinetic resolution of rac-epoxides by highly enantioselective EHs provides an environment-friendly bioprocess for the preparation of (R)-or (S)-epoxides with an intrinsic limitation of 50% yield 11 . However, the majority of wild-type (WT) EHs displayed unsatisfactory catalytic activity and/or E value, making them unable to be effectively used in the kinetic resolution of rac-epoxides 12 .…”
mentioning
confidence: 99%